Communication in the clinic: Negotiating nursing practice in sexual health clinics. (2nd January 2019) - Brunton, Margaret; Cook, Catherine
ABSTRACT: This article examines the tensions that can arise when managing the gulf between biomedicine and embodied nursing practice within a clinical context. We employ a thematic analysis of interview data from 6 nurses and 16 women attending 2 sexual health clinics in New Zealand. Four themes were identified. First, power of the gaze, and second, citizenship of the docile body illustrate the scientific, measurable context of biomedicine. Two further themes of entering the embodied lifeworld and neutralizing the power of the gaze give visibility to assumptions about the construction of meaning. The findings make two distinctive contributions. First, embodied communication challenged the omnipresent biomedical imperatives increasing agency for women. Second, despite positive outcomes, women still appealed to a biomedical paradigm as a beneficial adjunct to their clinical experience. Managers will benefit from recognizing the simultaneous presence of apparently competing paradigms of practice can enhance women's experiences in clinical environments.